2020
DOI: 10.3897/pharmacia.67.e56788
|View full text |Cite
|
Sign up to set email alerts
|

A geranylated chalcone with antiplatelet activity from the leaves of breadfruit (Artocarpus altilis)

Abstract: Platelet plays a crucial role in cardiovascular diseases (CVDs) development. Abnormalities in platelet aggregation provokes thromboembolism, eventually leading to death. In Indonesia, breadfruit (Artocarpus altilis) leaf is traditionally used to treat CVDs. This study aimed to evaluate the antiplatelet activity of A. altilis leaf extract (AAE) and to identify its active compound. A. altilis leaves were extracted with ethanol, and the antiplatelet activity was assessed using ADP-induced platelet aggregation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
7
0
5
Order By: Relevance
“…Daun sukun yang diekstraksi dengan metanol dan dipartisi dengan kloroform dapat ditemukan adanya senyawa auron H, auron I dan auron J serta 2 senyawa flavonoid yaitu 8-geranil-4',5,7trihidroksiflavon dan sikloaltilisin 7 [25]. Fraksi etil asetat mengandung senyawa geranil dihidrokalkon yang dilaporkan merupakan senyawa utama dalam daun sukun [26]. Senyawa lain yang berhasil diisolasi dari buah dan kulit pohon sukun adalah senyawa golongan terpenoid dengan kerangka sikloartan yaitu sikloartenol [21], sikloeukalenol, 2,4-metilensikloartenon, dan sikloartenon [27].…”
Section: Sukununclassified
“…Daun sukun yang diekstraksi dengan metanol dan dipartisi dengan kloroform dapat ditemukan adanya senyawa auron H, auron I dan auron J serta 2 senyawa flavonoid yaitu 8-geranil-4',5,7trihidroksiflavon dan sikloaltilisin 7 [25]. Fraksi etil asetat mengandung senyawa geranil dihidrokalkon yang dilaporkan merupakan senyawa utama dalam daun sukun [26]. Senyawa lain yang berhasil diisolasi dari buah dan kulit pohon sukun adalah senyawa golongan terpenoid dengan kerangka sikloartan yaitu sikloartenol [21], sikloeukalenol, 2,4-metilensikloartenon, dan sikloartenon [27].…”
Section: Sukununclassified
“…10 Another study showed the oedema reduction in rat paw oedema experimental model treated with 140 mg/kg BW of C. atropurpureus water extract. 12 In addition, a combination of the water extract of C. atropurpureus leaf with other herbal medicine, Clitoria ternatea flower at the dose of 328 mg/kg BW was able to reduce paw oedema with 9.1 mg/kg BW of Potassium diclofenac in mice. 11 In this study, the investigation of the anti-inflammatory activity of C. atropurpureus leaf was done by testing the ethanol extract (EE), nhexane fraction (HF), and ethanol-water fraction (EWF) in carrageenan-induced paw oedema in rat.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study reported that C. atropurpureus contained flavonoid, saponin, polyphenol, and terpenoid in the leaves of C. atropurpureus. 11,12 The water extract of C. atropurpureus (at the doses of 100; 200; dan 400 mg/kg BW) demonstrated anti-inflammatory effect. 10 Another study showed the oedema reduction in rat paw oedema experimental model treated with 140 mg/kg BW of C. atropurpureus water extract.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones are used in several biosynthetic pathways as initial intermediate structures in the production of flavonoids, isoflavonoids, and aurones . A significant part of medicinal chemistry research in the 21st century has been focused on both natural and synthetic chalcones because of their various pharmacological potential including activities and characteristics such as antibacterial, anti-inflammatory, analgesic, , anticholinergic, antiplatelet, antiulcer, antioxidant, , antimalarial, anticancer, , antiviral, antileishmanial, antidiabetic, , immunomodulatory, , aldose reductase inhibition, estrogenic, acetylcholinesterase inhibition, and as non-purine xanthine oxidase inhibitors . Chalcones are highly attractive molecules because of their simple structure, ease of construction, and promising biological applications.…”
Section: Introductionmentioning
confidence: 99%